Field report PAC 671: Muhibbin Group Sdn. Bhd. / ‘Aliah Aisyah Kamaruzaman - Kamaruzaman, ‘Aliah Aisyah (Universiti Teknologi MARA, Terengganu, 2024)
Muhibbin Associates SDN BHD was established in 2011 under the Companies Act 1965. The company was renamed Muhibbin Group SDN BHD in 2019, and it is currently led by Mr Mohammad Baihaqi Hassanuddin as Managing Director and two other Directors, Mr Khairul Anuar Jamaludin and Mr Luqmannulhakim Mohd Halim. The vision of Muhibbin Group Sdn Bhd is to establish a company that offers global corporate services in the areas of secretarial, financial, self-development, and mind. The company's mission is to unite professional and semi-professional workforces in secretarial, financial, taxation, and self-development and mind under a single organisation while fostering a comfortable work environment and assisting one another in achieving the company's vision. It is located at E-21-1, Blok 3, Jalan Serai Wangi M16/M, Alam Avenue 2, Seksyen 16, 40200 Shah Alam, Selangor. Next, Muhibbin Group Sdn Bhd provides five services, which are company registration, Ministry of Finance (MOF) registration, Contractor Service Centre (PKK) and Construction Industry Development Board (CIDB) registration, company administration, and company secretary. Additionally, this company provides a wide range of benefits, such as opportunities to become staff, a pantry section, lunch provided, a dormitory near the office, a broad exposure where you can learn from industry professionals across various aspects of accounting, and an allowance ranging from RM300 to RM1,000 for trainees.